Effective and Affordable Methodologies for the Optical Characterization of Envelope Materials Within Urban Contexts - Noelia Alchapar; Fernando Martín-Consuegra; Ayelén Villalba; Carmen Alonso; Cláudia Pezzuto; Borja Frutos; Gloria Pérez (Urban Science)
The optical properties of urban envelope materials play a significant role in determining the energy balance of cities. The effective management of solar energy through these materials can help mitigate the urban heat island effect (UHI) and improve thermal comfort in urban spaces. The main objective of this study is to determine reliable methodologies for the optical characterization of opaque façade and pavement materials within urban enclosures. These methodologies should be cost-effective for implementation in emerging economies, enabling the collection of precise data for the development of urban energy simulation models. A social neighborhood in the city of Mendoza, Argentina, was selected as the case study. The optical properties of façade and pavement materials were characterized by spectrometric analysis (solar and visible reflectance, color coordinates) and in situ thermal emissivity. This research provides essential data for the development of more precise building and city simulation models, as well as for the identification of optimal materials to replace existing ones in the pursuit of strategies to reduce energy demand and enhance the urban microclimate.